SELF REGULATED LEARNING DAN LITERASI DIGITAL TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS SEBELAS MARET SURAKARTA APAKAH BERPENGARUH? - Daud Adi Prasaja, Daud Adi Prasaja; Sudarno; Dini Octoria (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to determine (1) the effect of self-regulated learning on the learning achievement of students of Economic Education at Sebelas Maret University, Surakarta, (2) the effect of digital literacy on the learning achievement of students of Economics at Sebelas Maret University, (3) the effect of self-regulated learning and digital literacy in a simultaneously on the learning achievement of students of economic education at Eleven March University. This research is a quantitative descriptive study with a population of 302 economics students from the 2020, 2021, and 2022 batches. The sampling technique used in this study was Proportional Random Sampling which resulted in 172 students. Data collection is carried out through questionnaires or questionnaires which are distributed via the Google form link. The data analysis used was multiple linear regression analysis with SPSS 25.The results shown from this study are: (1) First, self-regulated learning has a positive effect on the learning achievement of students of economic education at Sebelas Maret University, then (2) digital literacy has a positive and significant effect on the learning achievement of students of economic education at Sebelas Maret University, ( 3) self-regulated learning and digital literacy have a joint effect on the learning achievement of students of economic education at Sebelas Maret University.